(untitled) (Journal of Health Sciences, 2015)
A 32-years old woman presented to the emergency room of Bozok University Research Hospital with right renal colic. Multidetector computed tomography (MDCT) showed compression of the proximal ureter by the right ovarian vein and compression of the right distal ureter by the right external iliac vein. To the best of our knowledge, right proximal ureteral compression by the ovarian vein together with distal ureteral compression by the external iliac vein have not been reported in the literature. Ovarian vein and external iliac vein compression should be considered in patients presenting to the emergency room with renal colic or low back pain and a dilated collecting system.